ANALISIS EFEKTIVITAS SISTEM MAINTENANCE SEBAGAI UPAYA PENINGKATAN KINERJA OPERASIONAL MELALUI MAINTENANCE 4.0 - Tashadda Qanitan; Mohammad Agung Saryatmo; Lithrone Laricha Salomon (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
The Industry 4.0 era demands a transformation of machine maintenance systems from reactive to predictive to maintain production efficiency. This research focuses on Flexographic Printing machines in the packaging industry, which are experiencing low performance with an average Overall Equipment Effectiveness (OEE) value of only 49.78%, far below global standards. The objective of this research is to enhance maintenance effectiveness through the development of a Smart Maintenance framework named